Hammer-shaped slotted antenna design and analysis for wireless applications - Gajendran Srihari; Raman Ramamoorthy; Shanmuganantham Thangavelu; Nimmagadda Padmaja (Institute of Advanced Engineering and Science, 2023)
The method for creating a two-element multiple-input and multiple-output (MIMO) ultra-wideband hammer antenna is presented in this paper. It has been suggested to investigate characteristics of this ultra-wideband antenna design. Split-ring resonators (SRR), made of metamaterial, have enhanced performance of antenna in terms of multiplexing effectiveness, S parameters, radiation characteristics, envelope correlation coefficient, and diversity gain. Reduced weight and size of this antenna technology make it easier to integrate into a 5G and linked object receiver. Because the outputs from the previous designer to the target entity did not satisfy the standards, we thoroughly researched design attributes and made parametric changes to the design to reach the precise outcomes.